1983
DOI: 10.1152/jappl.1983.55.4.1321
|View full text |Cite
|
Sign up to set email alerts
|

Role of alveolar recruitment in lung inflation: influence on pressure-volume hysteresis

Abstract: The behavior of terminal lung units (alveoli) with changes in lung volume is controversial. For example, different investigators using similar techniques have suggested that alveoli expand homogeneously or, conversely, get smaller with increases in lung volume. We studied this problem by filling excised dog lobes with monodisperse aerosol and observing deposition at zero airflow. Under these conditions, the deposition of particles is inversely proportional to a mean alveolar linear dimension (ALD). With this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
37
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 0 publications
7
37
0
Order By: Relevance
“…18 Th us, unless the lung volumes are matched carefully, it is not possible to compare CT scan densities from diff erent individuals. TLC is based on a voluntary eff ort, and there is considerable variability in this eff ort among individuals that is likely greater in people with lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…18 Th us, unless the lung volumes are matched carefully, it is not possible to compare CT scan densities from diff erent individuals. TLC is based on a voluntary eff ort, and there is considerable variability in this eff ort among individuals that is likely greater in people with lung disease.…”
Section: Discussionmentioning
confidence: 99%
“…By matching this degree of geometric hysteresis, we have generated physiologically realistic asynchrony in physical models (41) and computational models (16), which demonstrated that geometrical hysteresis, even if small, can produce stretchand-fold patterns and, consequently, induce substantial acinar flow irreversibility. In a related work, Smaldone et al (31), using gravitational sedimentation of aerosol particles to estimate mean linear intercepts, showed significant geometric hysteresis in excised lungs with large-volume excursions from minimal volume and interpreted their data in terms of respiratory unit recruitment and derecruitment. Those studies, however, being restricted to single-volume histories, did not address the issue of mixing during cyclic ventilation and so are not strictly comparable to the present work.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the recruited ∆Vs has been predicted to be a power law with an exponent of 2 [21] and has recently been measured indirectly [6]. Our data reflect a direct assessment of the distribution of alveolar recruited ∆Vs.…”
supporting
confidence: 67%
“…Nevertheless, for the first inflation, the data were in excellent agreement with the model prediction [21] since the theoretical value of the exponent is 2, whereas the estimated average one was 2.02. The distribution obtained from the second inflation had an exponent of 1.88, which is also close to the theoretical value of 2.…”
supporting
confidence: 66%
See 1 more Smart Citation